The origins of late-twentieth-century variations in the large-scale north Atlantic circulation - Yeager, Stephen (author); Danabasoglu, Gokhan (author) (Journal of Climate, 2014)
Surface forcing perturbation experiments are examined to identify the key forcing elements associated with late-twentieth-century interannual-to-decadal Atlantic circulation variability as simulated in an ocean-sea ice hindcast configuration of the Community Earth System Model, version 1 (CESM1). Buoyancy forcing accounts for most of the decadal variability in both the Atlantic meridional overturning circulation (AMOC) and the subpolar gyre circulation, and the key drivers of these basin-scale circulation changes are found to be the turbulent buoyancy fluxes: evaporation as well as the latent and sensible heat fluxes. These three fluxes account for almost all of the decadal AMOC variability in the North Atlantic, even when applied only over the Labrador Sea region. Year-to-year changes in surface momentum forcing explain most of the interannual AMOC variability at all latitudes as well as most of the decadal variability south of the equator. The observed strengthening of Southern Ocean westerly winds accounts for much of the simulated AMOC variability between 30°S and the equator but very little of the recent AMOC change in the North Atlantic. Ultimately, the strengthening of the North Atlantic overturning circulation between the 1970s and 1990s, which contributed to a pronounced SST increase at subpolar latitudes, is explained almost entirely by trends in the atmospheric surface state over the Labrador Sea.